2000
DOI: 10.3130/aijt.6.111_1
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment on Elasto-Plastic Behavior of a Full-Scale Three-Story Two-Bay Composite Frame Structure Consisting of Reinforced Concrete Columns and Steel Beams

Abstract: Full sea1 θ test , Three story and two bay frame, Composite structure consist − ing of steel beams and reinferced concr θ te columns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To learn more about the cyclic performance of RCS moment frames in the building structures, a series of tests have been conducted [33][34][35][36][37][38][39]. Te results reported that (1) the frame structures with two joint details of through-beam type and through-column type had an excellent seismic performance, those of which presented the plastic hinge mechanisms that concentrated upon the end of steel beams and the bottom of RC columns to meet the strong-joint weak-component criterion; (2) the structure slightly damaged in frequent earthquake and presented the collapse prevention level under rare earthquake to further validate the reliability of this innovative system.…”
Section: Introductionmentioning
confidence: 99%
“…To learn more about the cyclic performance of RCS moment frames in the building structures, a series of tests have been conducted [33][34][35][36][37][38][39]. Te results reported that (1) the frame structures with two joint details of through-beam type and through-column type had an excellent seismic performance, those of which presented the plastic hinge mechanisms that concentrated upon the end of steel beams and the bottom of RC columns to meet the strong-joint weak-component criterion; (2) the structure slightly damaged in frequent earthquake and presented the collapse prevention level under rare earthquake to further validate the reliability of this innovative system.…”
Section: Introductionmentioning
confidence: 99%
“…16 They had different joint details but the same scale with two-story and two-bay; the test results indicated that two frame specimens exhibited good seismic behavior. Yamamoto et al 17 conducted a cyclic loading test of an RCS frame with three-story and two-bay. The experimental results showed that RCS joints did not become seriously damaged, and the frame specimen presented good ductility and energy dissipation.…”
Section: Introductionmentioning
confidence: 99%